The Implications of Financial Asset and Housing Markets on Profit- and Wage-led Growth: Some Results in Comparative Statics - Amit Bhaduri (The Vienna Institute for International Economic Studies (wiiw), 2010)
This paper presents a number of extensions to the theory of profit- and wage-led growth by integrating selected aspects of asset markets and housing markets. Theoretical results from comparative statics are then presented and discussed, notably with reference to recent housing market bubbles. The exposition incorporates distributional aspects relating to different classes of economic agents and how those differences relate to wage income versus profit income.
Keywords: G12; E21; E25; E22; 330; profit-led growth; wage-led growth; asset market; housing market; stability; forced saving; profit squeeze; distribution and growth theories; effective demand